Junctional Kyphosis after Long Segment Fusion. Issue 1 (April 2016) - El-Sharkawi, Mohammad; Gad, Wael; Elkott, Amer; Tammam, Hamdy; El-Meshtawy, Mohamed
Introduction: The incidence of junctional kyphosis (JK) varies in the literature from 7% to 40%. We here present our experience with JK. The aim of this work is investigate the incidence of JK after long spinal segment fusion, to identify the underlying factors leading to its development, and to discuss treatment outcome. Patients and Methods: This combined retrospective/prospective cohort study included sixty-four consecutive patients (40 women and 24 men) with a mean age of 20.7 years, who underwent long segment spinal fusion (≥ 5 vertebrae) for treatment of spinal deformity. The average length of follow-up was 2 years. Risk factors analyzed included patients' factors, surgical factors, and radiographical parameters such as thoracic kyphosis (TK), lumbar lordosis (LL), sagittal vertical axis, pelvic tilt, and pelvic incidence. Results: Radiological JK occurred in 14 patients (22%). Ten cases were proximal junctional kyphosis (PJK), two cases were intercalary junctional kyphosis (IJK), and two cases were distal Junctional Kyphosis (DJK). Only seven patients (50%) out of the 14 with JK were symptomatic. Six cases have undergone revision surgery. In nine cases, the original deformity was kyphosis (1 Ankylosing spondylitisS, 1 post-tuberculous, 3 Sheuermann's kyphosis, 4 congenital kyphosis). The other 5 cases were scoliosis (3 idiopathic and 2 congenital). Preoperative TK more than 40 ° was associated with PJK. In all cases PI, PT, SS, SVA were within normal range, but it was noticed that SVA had negative values in 5 cases. LIV in the dorsolumbar junction was associated with DJK. Conclusion: Pre-existing TK more than 40°was identified as an independent risk factor. Negative sagittal balance may be a risk factor for PJK. A surgical strategy to minimize Junctional kyphosis may include careful preoperative planning for reconstructions with a goal of optimal postoperative alignment.